A Comprehensive Overview of Activities of Daily Living in Existing Frailty Instruments: A Systematic Literature Search. (17th December 2019) - Costenoble, Axelle; Knoop, Veerle; Vermeiren, Sofie; Vella, Roberta Azzopardi; Debain, Aziz; Rossi, Gina; Bautmans, Ivan; Verté, Dominique; Gorus, Ellen; De Vriendt, Patricia
Abstract: Background and Objectives: The relationship between frailty and disability in activities of daily living (ADLs) can be seen in different ways, with disability being—to varying degrees—a characteristic, negative outcome, or predictor of frailty. This conflation of definitions is partly a result of the different frailty tools used in research. Aiming to provide a comprehensive overview, this systematic literature search analyzed (i) if, (ii) to what extent, and (iii) how ADLs are evaluated by frailty instruments. Research Design and Methods: A search was performed in PubMed, Web of Knowledge, and PsycINFO to identify all frailty instruments, followed by categorization of the ADL items into basic (b-), instrumental (i-), and advanced (a-) ADLs. Results: In total, 192 articles described 217 frailty instruments, from which 52.1% contained ADL items: 45.2% b-ADLs, 35.0% i-ADLs, and 10.1% a-ADLs. The most commonly included ADL items were bathing (b-ADLs); using transportation (i-ADLs); and semiprofessional work engagement in organized social life or leisure activities (a-ADLs). These instruments all had a multidomain origin (χ 2 = 122.4, p < .001). Discussion and Implications: Because 52.1% of all instruments included ADL items, the concepts of frailty and disability appear to be highly entangled. This might lead to circular reasoning, serious concerns regarding contamination, and invalid research results.